A versatile, compartmentalised gut-on-a-chip system for pharmacological and toxicological analyses - Pim de Haan (Nature Portfolio, 2021)
Abstract A novel, integrated, in vitro gastrointestinal (GI) system is presented to study oral bioavailability parameters of small molecules. Three compartments were combined into one hyphenated, flow-through set-up. In the first compartment, a compound was exposed dynamically to enzymatic digestion in three consecutive microreactors, mimicking the processes of the mouth, stomach, and intestine. The resulting solution (chyme) continued to the second compartment, a flow-through barrier model of the intestinal epithelium allowing absorption of the compound and metabolites thereof. The composition of the effluents from the barrier model were analysed either offline by electrospray-ionisation-mass spectrometry (ESI–MS), or online in the final compartment using chip-based ESI–MS. Two model drugs, omeprazole and verapamil, were used to test the integrated model. Omeprazole was shown to be broken down upon treatment with gastric acid, but reached the cell barrier unharmed when introduced to the system in a manner emulating an enteric-coated formulation. In contrast, verapamil was unaffected by digestion. Finally, a reduced uptake of verapamil was observed when verapamil was introduced to the system dissolved in apple juice, a simple food matrix. It is envisaged that this integrated, compartmentalised GI system has potential for enabling future research in the fields of pharmacology, toxicology, and nutrition.